2021
DOI: 10.4062/biomolther.2020.212
|View full text |Cite
|
Sign up to set email alerts
|

Abuse Potential of Synthetic Cannabinoids: AM-1248, CB-13, and PB-22

Abstract: Currently, the expanding recreational use of synthetic cannabinoids (SCBs) threatens public health. SCBs produce psychoactive effects similar to those of tetrahydrocannabinol, the main component of cannabis, and additionally induce unexpected pharmacological side effects. SCBs are falsely advertised as legal and safe, but in reality, SCB abuse has been reported to cause acute intoxication and addictive disorders. However, because of the lack of scientific evidence to elucidate their dangerous pharmacological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…This is consistent with previous studies showing that addictive SCBs, such as JWH-018 and WIN 55,212-2, support IVSA [22,23]. In addition, Mepirapim treatment-induced impulsive behaviours identified by multiple inactive lever presses, which are also induced by other SCBs treatment [20]. These impulsive behaviours are frequently observed in SCB users and are considered to increase the risk of recreational abuse of the drug [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with previous studies showing that addictive SCBs, such as JWH-018 and WIN 55,212-2, support IVSA [22,23]. In addition, Mepirapim treatment-induced impulsive behaviours identified by multiple inactive lever presses, which are also induced by other SCBs treatment [20]. These impulsive behaviours are frequently observed in SCB users and are considered to increase the risk of recreational abuse of the drug [24].…”
Section: Discussionsupporting
confidence: 90%
“…These results indicate that Mepirapim is an addictive drug with reinforcing effects [19]. Furthermore, the average number of inactive lever presses was significantly higher in the Mepirapim groups (0.01 and 0.03 mg•kg −1 •inf −1 ) than in the vehicle group (Figure 2D, F (3,16) = 3.8, p < 0.05), indicating that Mepirapim induces impulsive behaviours similar to those induced by treatment with other SCBs [20]. Two-way ANOVA revealed statistically significant effects from drug treatment (F (3,16) = 3.8, p < 0.05) and day (F (6,96) = 3.58, p < 0.05), but no significant effect of their interaction was observed (F (18,96) = 0.81, p = 0.69).…”
Section: Mepirapim Treatment Supported Maintenance Of Ivsa In Ratsmentioning
confidence: 73%
“…Cryab KO mice exhibited potentially higher sensitivity to the addiction-related effects of JWH-018, as evidenced by their increased responses in intravenous SA ( Figures 3A–C ) and CPP ( Figure 3E ) tests compared to WT mice. While several studies have reported the addiction-like effects of synthetic cannabinoids, including JWH-018 ( Hur et al, 2021 ), in healthy rodent subjects ( Cha et al, 2014 ; de Luca et al, 2015 ), some cannabinoids still do not exhibit significant abuse potential in animal behavioral paradigms ( Tampus et al, 2015 ; Bilel et al, 2019 ). This suggests the involvement of complex neurological mechanisms (that mediate the addictive effects of cannabinoids) other than the typical mesolimbic dopaminergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a misleading term, as psychoactive properties are not the only desirable trait, even if they are the most popular trait of these compounds. Several inert cannabinoids have not been characterized in depth despite interesting pharmacology [4,6,9,11,54,59]. To add to the complexity of the presented landscape, cannabinoids can be synthesized de novo [10,43].…”
Section: Types Of Cannabinoidsmentioning
confidence: 99%
“…Several inert cannabinoids have not been characterized in depth despite interesting pharmacology [4,6,9,11,54,59]. To add to the complexity of the presented landscape, cannabinoids can be synthesized de novo [10,43].…”
Section: Types Of Cannabinoidsmentioning
confidence: 99%